PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP KELENGKAPAN PENGUNGKAPAN DALAM LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Pranesti, Anasya Bimbi; Widiawati, Hestin Sri; Solikah, Mar'atus (Universitas Nusantara PGRI Kediri, 2022)
This study aims to analyze the factors that influence the Completeness of Disclosures in the Annual Report based on the characteristics of the company. The research methodology approach uses a quantitative approach with associative research techniques. The population in this study took manufacturing companies listed on the IDX with a research sample of 52 companies in 2019-2020. Hypothesis testing in this study used logistic regression test statistics. The results of the analysis conclude that the variables of Firm Size and Solvency Ratio have a positive effect on the level of completeness of Disclosures in the Annual Report. While the variables of Liquidity Ratio, Profitability Ratio, and Company Status have no effect on the level of completeness of Disclosures in the Annual Report in manufacturing companies.